Roles of Collagen XXV and Its Putative Receptors PTPσ/δ in Intramuscular Motor Innervation and Congenital Cranial Dysinnervation Disorder - Haruka Munezane; Hiroaki Oizumi; Tomoko Wakabayashi; Shu Nishio; Tomoko Hirasawa; Takashi Sato; Akihiro Harada; Tomoyuki Yoshida; Takahiro Eguchi; Yuji Yamanashi; Tadafumi Hashimoto; Takeshi Iwatsubo (Cell Reports, 2019)
Summary: Intramuscular motor innervation is an essential process in neuromuscular development. Recently, mutations in COL25A1, encoding CLAC-P/collagen XXV, have been linked to the development of a congenital cranial dysinnervation disorder (CCDD). Yet the molecular mechanisms of intramuscular innervation and the etiology of CCDD related to COL25A1 have remained elusive. Here, we report that muscle-derived collagen XXV is indispensable for intramuscular innervation. In developing skeletal muscles, Col25a1 expression is tightly regulated by muscle excitation. In vitro and cell-based assays reveal a direct interaction between collagen XXV and receptor protein tyrosine phosphatases (PTPs) σ and δ. Motor explant assays show that expression of collagen XXV in target cells attracts motor axons, but this is inhibited by exogenous PTPσ/δ. CCDD mutations attenuate motor axon attraction by reducing collagen XXV-PTPσ/δ interaction. Overall, our study identifies PTPσ/δ as putative receptors for collagen XXV, implicating collagen XXV and PTPσ/δ in intramuscular innervation and a developmental ocular motor disorder. : Munezane et al. demonstrate essential roles of muscle-derived collagen XXV in motor axon attraction and intramuscular innervation during development. Collagen XXV interacts with motor axons through its putative receptors PTPσ/δ. Congenital cranial dysinnervation disorder-causing mutations in collagen XXV attenuate the interaction with PTPσ/δ and disrupt innervation by motor axons. Keywords: motor neuron, neuromuscular development, collagen, receptor protein tyrosine phosphatase